Pengaruh Tax Avoidance terhadap Nilai Perusahaan Dimoderasi oleh Profitabilitas terdaftar di Bursa Efek Indonesia - Khrisna Anggun Yuliana; Ng Husin (LPPM STIE PPI, 2024)
Introduction/Main Objectives: To examine the effect of tax avoidance practices on company value in the agricultural sector, especially palm oil, listed on the Indonesia Stock Exchange. Background Problems: Tax avoidance practices can be viewed as management efforts to maximize personal welfare, but this practice can have a negative impact on company value in the long term. Novelty: This study does not only stop at analyzing the relationship between tax avoidance and company value, but also explores more deeply the role of profitability as a moderating variable. Research Methods: Purposive sampling is used to select samples of companies that meet certain criteria with analysis carried out using multiple linear regression, by first conducting a classical assumption test. Findings/Results: Shows that tax avoidance can have a positive impact on company value, and profitability can strengthen the relationship between tax avoidance and company value. Conclusion: Efficiency practices in financial management through tax avoidance can increase company value in the context of the Indonesian palm oil industry.